Status of village goat management practices in Maharashtra - GOKHALE, S B; GOKHALE, R B; PHADKE, N L; DESALE, R J (The Indian Journal of Animal Sciences, 2014)
Rural families (421) from Ahmednagar, Pune, Satara, Solapur and Thane districts in Maharashtra state were surveyed to study the status of goat breeders, goats and their breeding. feeding, management and health aspects. The survey revealed that the average large dairy animal holding of the goat keeper was 5.67Â± 0.41 which constituted 2.17% of his livestock holding while that of small ruminants was 22%. The literacy rate among the families was 59%. Amongst the literate 39% were educated up to primary education level, while 20% were educated up to high school. There was no effect of the education and age on the number of animals reared by the goat keeper. 53.68% of the goat rearcrs maintained their own bucks for breeding. The goat rearers having no breeding facility (45.60%) paid from Rs 5 to 90 per service for breeding their does. Most of goats were housed in special thatch shelter (46.9%). followed by thorny compound (35.86%); some used their residence (14.48%). Only 9.2% constructed permanent cement houses for their goats. Only 39.9% studied goat rearers vaccinated their goats for various diseases like FMD, HS 8Q, enterotoximiea and pox. Amongst diseases noticed by rearers, diarrhoea was the most common followed by FMD, paralysiS and vesicles on mouth. Home remedies are resorted to. It was concluded that rural illiterate unemployed people looking to goat as a tool for livelihood. require increased awareness in goat breeding, feeding and management. Appropriate training and extension efforts can go long way in using goat rearing as a toof for rural employment.